Kekerasan Pada Anak dan Dampaknya Terhadap Anak yang Dialami Bocah 10 Tahun di Bekasi Tahun 2023 - Pakpahan, Agustinus; Yunus, Hudi (Media Hukum Indonesia (MHI), 2025)
Parents often commit acts of violence against children, although the goal is to educate but most parents take the wrong steps, as a result many children experience trauma and child development worsens due to the violence given when they were little. Many habits are often dangerous for children but parents are often not aware of it, so many children get bad impacts from these habits. Parents should be more careful in taking a stance towards their students, and this is very important because it greatly affects the child's future development. Although most parents are not aware that what is given to children has a great influence on children both mentally and physically.